Sítios históricos brasileiros: monumento, documento, empreendimento e instrumento - o caso de Sobral/CE - Duarte Junior, Romeu (2012)
This work ("Brazilian Historic Sites: Monument, Document, Enterprise and Instrument: The case of Sobral/CE") deals with relations established between the preservation of the built cultural heritage and urban planning and management of historic site of Sobral, protected as nacional monument by Instituto do Patrimônio Histórico e Artístico Nacional - IPHAN since 1999. Emphasizing new approaches of the federal listing of urban areas in Brazil and other countries, in its political, administrative and changing aspects, SObral urban preservation experience is analized through the concepts of cidade-monumento, cidade-documento, cidade-empreendimento e cidade-instrumento,this the main hipotesis of the work.